A novel approach to volcano surveillance using gas geochemistry - Moussallam, Yves; Oppenheimer, Clive; Scaillet, Bruno (Comptes Rendus. Géoscience)
Identifying precursory phenomena is central to the short-range assessment and anticipation of volcanic hazards. The chemistry of gases, which may separate from magma at depth, is operationally monitored at many volcanoes worldwide to manage risk. However, owing to the complexity of volcanic degassing, decoding the message of gas geochemistry has proven challenging. Here, we report an approach to restoration of measured volcanic gas compositions that enables tracking of variations in the temperature and/or oxidation state of the source magma. We validate the approach with reference to independent estimates of melt oxidation state obtained by X-ray absorption near-edge structure (XANES) spectroscopy at the iron K-edge. We then apply the method to a global database of high temperature volcanic gases and to extended gas geochemical timeseries at Unzen, Aso, and Asama volcanoes, identifying hitherto unreported but significant changes in magma intensive parameters that preceded or accompanied changes in volcanic activity. Restoration of volcanic gas compositions offers a promising complement to monitoring strategies at active volcanoes, calling for more systematic operational surveillance of redox-sensitive gas species.